Uji Formulasi Sediaan Salep Ekstrak Batang Brotowali (Tinospora Crispa L. Miers ) Kombinasi Zeolit Terhadap Bakteri Staphylococcus Aureus dan Pseudomonas Aeruginosa - Laila Susanti; Subur Widodo; Syaiful Bahri; Wenny Indriasari (Inovasi Pembangunan : Jurnal Kelitbangan, 2016)
Treatment of infected wounds on the skin generally use synthetic chemicals, which when used in the long term lead to negative side effects. Development of herbal medicines have been done as an alternative to synthetic chemicals because of cheap and has no side effects and low toxicity. From this background, the test formulation extract ointment preparation brotowali (Tinospora crispa L. Miers) a combination of zeolite against Staphylococcus aureus and Pseudomonas aeruginosa in vitro. This study aims to get the best formulation of the extract ointment preparation brotowali (Tinospora crispa L. Miers) which has an antibacterial effect against Staphylococcus aureus and Pseudomonas aeruginosa. In this study, the method used discs to observe the growth of bacteria by doing two to three treatments. P1 was the treatment group were given a salve on the market, namely the ointment Gentamicin as a positive control, P2 is the treatment group were given an ointment containing extract brotowali combination of zeolite with base oils, P3 is the treatment group were given ointment without extract brotowali oily base as a negative control. From the research results generated extract ointment brotowali with base oils produced are bactericidal and active substance formulations extract brotowali combination of zeolite that is at 9%v/v.